Formulation, Development Optimization of Miconazole Tablets for Buccal Drug Delivery System - Sunil Reddy (Journal of Global Pharma Technology, 2017)
Objective the main objective of the present study was to develop sustained release formulation of Miconazole to maintain constant therapeutic levels of the drug for over 10 hrs. Method various grades of HPMC were employed as polymers. Miconazole dose was fixed as 100 mg. Total weight of the tablet was considered as 250 mg. Polymers were used in the concentration of 50 mg, 75mg and 100 mg concentration. All the formulations were passed various physicochemical evaluation parameters and they were found to be within limits. Results From the dissolution studies it was evident that the formulation (F2) showed better and desired drug release pattern i.e., 98.56 % in 10 hours. Conclusion From the dissolution data it was evident that the formulations prepared with HPMC K100M as polymer were unable to retard the drug release up to desired time period i.e., 10 hours. Whereas the formulations prepared with HPMC K4M retarded the drug release in the concentration of 75 mg showed required release pattern i.e., retarded the drug release up to 10 hours and showed maximum of 98.56% in 10 hours with good retardation. It followed zero order release kinetics mechanism.Keywords: Miconazole, HPMC, Buccal Tablets.